Strategi Pemulihan Berkelanjutan melalui Program Pemberdayaan: Studi pada Petani Bawang dan Coklat di Wilayah Pascabencana Sulawesi Tengah - Apriani, Resti Mirza (Jurnal Ilmu Kesejahteraan Sosial, 2025)
Natural disasters in Central Sulawesi in 2018 damaged the onion and cocoa farming sectors, which are the main sources of livelihood for the local communities. Post-disaster economic recovery requires sustainable empowerment programs, such as access to capital, agricultural technology, and training to enhance farmers’ capacity. BAZNAS collaborated with PT Sarana Multi Infrastruktur (SMI) through SMI’s CSR program to implement an empowerment initiative for onion farmers in Guntarano Village (Tanantovea Subdistrict, Donggala Regency) and Duyu Subdistrict (Tatanga Subdistrict, Palu City), as well as cocoa farmers in Tuva Village (Gumbasa Subdistrict, Sigi Regency), areas affected by the Central Sulawesi earthquake. This study examines the sustainable recovery strategies through this empowerment program. Using a qualitative case study approach, data were collected through documentation, interviews, focus group discussions, and field observations in the three affected areas: Guntarano, Duyu, and Tuva. The results show that the empowerment program significantly improved farmers' economic conditions, skills, social capital, and well-being, while also promoting environmentally friendly practices such as the use of organic fertilizers and waste management. Community participation, capacity building, and cross-sector collaboration were key factors in the program’s success and sustainability. This study highlights the importance of structured empowerment models, reliable field facilitators, and inclusive policy support to ensure the long-term resilience of farming communities in disaster-prone areas.